CD32a receptor in health and disease - N. A. Arsentieva; O. K. Batsunov; I. V. Kudryavtsev; A. V. Semenov; Areg A. Totolian (Медицинская иммунология)
Low-affinity Fcγ-receptors that recognize the Fc portion of immunoglobulin (Ig) molecules, usually being in antigen-bound state, thus representing a link between innate and adaptive immunity. They play a significant role in inflammatory and infectious diseases. Among them, a separate FcγRII family (CD32) is discerned, which is characterized by transmission of intracellular signal independently of the common γ-chain, they have one α-chain containing two extracellular immunoglobulin-like domains. FcγRII receptors are present in almost all cells of the innate immune system: monocytes and macrophages, neutrophils, eosinophils, dendritic cells, as well as on B-lymphocytes and platelets. They perform two main functions: target recognition, facilitation of phagocytosis and destruction of antibody-opsonized cells by monocytes/ macrophages (including pathogenic cells). In parallel, the phagocytes are activated via the cytokine synthesis stimulation. The FcγRIIA (CD32a) and FcγRIIC (CD32c) activating receptors, like as FcγRIIB (CD32b) inhibiting receptors are present among the members of the FcγRII family. The low-affinity FcγRII receptors bind to IgG, with immune complexes being their natural ligands. High levels of immune complexes are usually found in both chronic viral infections and autoimmune diseases. There are shown polymorphic variants of the CD32a gene, which can affect the receptor function, and, thereby, causing susceptibility for different infections, influence the development of autoimmune diseases and primary immunodeficiencies. Activation of the CD32a receptor induces the production of pro-inflammatory cytokines, including TNFα and interferons, that are involved into inflammation in systemic lupus erythematosus, Kawasaki disease, Graves’ disease and rheumatoid arthritis. It has been shown that antibacterial activity of platelets is carried out via the CD32a receptor. The study of CD32a expression in people The CD32a receptor is considered a biomarker of cells that are a reservoir of HIV infection. At the present time, however, many questions remain regarding the mechanisms of CD32a expression of on HIV-infected cells and the role of CD32a in the formation of an HIV reservoir and/or development of appropriate resistance. In addition to HIV infection, the significance of FcγR receptors is shown in other infectious diseases, for example, with influenza and dengue virus infections. Better understanding of the CD32a structure and function will help to assess its role in immunopathogenesis of different conditions. This review focuses on the role of CD32a in development of the normal immune response in normal state and various diseases.